Wishypoofs and hiccups ebook Zoey and sassafras #9: zoey and sassafras series, book 9. - Citro, Asia (Zoey and Sassafras, 2021)
Oh dear . . . when Pip shows up with a new look that's just as much of a surprise to him as to Zoey and Sassafras, the trio knows something strange is happening in the forest. They retrace Pip's steps only to see another magical friend change right before their eyes! It's up to the team to figure out what is happening and how to change the magical animals back before things get any more serious . . . Each story in the Zoey and Sassafras series features a new magical animal with a problem that must be solved using science. There isn't a set formula for each book; Zoey sometimes needs to run experiments, while other times she needs to investigate a mystery, and yet other times she needs to do research. Zoey models how to keep a science journal through her handwritten entries in each story. Each story is complete with a glossary of the kid-friendly definitions for scientific terms used. The series highlights child-led inquiry science and the topics covered align with both Common Core and Next Generation Science Standards.